2016
DOI: 10.1002/mds.26808
|View full text |Cite
|
Sign up to set email alerts
|

Clinical exome sequencing in early‐onset generalized dystonia and large‐scale resequencing follow‐up

Abstract: Our study identified whole-exome sequencing as an effective strategy for molecular diagnosis of early-onset generalized dystonia and offers insights into the heterogeneous genetic architecture of this condition. Furthermore, it provides confirmatory evidence for a dystonia-relevant role of ANO3 and ADCY5, both of which likely associate with a broader spectrum of dystonic expressions than previously thought. © 2016 International Parkinson and Movement Disorder Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
106
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(117 citation statements)
references
References 47 publications
6
106
0
5
Order By: Relevance
“…Interestingly, this severely affected nonverbal and nonambulant patient received no therapeutic benefit from propranolol or from any other drug. However, the patients in this study did appear to benefit from deep-brain stimulation (DBS), as did another p.418W patient reported by Meijer et al [14]. Zech et al [15] identified seven early-onset generalised dystonia cases with novel ADCY5 mutations (c.2180G>A; p. R727K; c.1378A>T, p. I460F; c.1196C>T, p. P399L; c.1400A>G, p. N467S; c.3177_3182delTGA, p. D1060del; c.3625A>G, p. M1209V) [14].…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Interestingly, this severely affected nonverbal and nonambulant patient received no therapeutic benefit from propranolol or from any other drug. However, the patients in this study did appear to benefit from deep-brain stimulation (DBS), as did another p.418W patient reported by Meijer et al [14]. Zech et al [15] identified seven early-onset generalised dystonia cases with novel ADCY5 mutations (c.2180G>A; p. R727K; c.1378A>T, p. I460F; c.1196C>T, p. P399L; c.1400A>G, p. N467S; c.3177_3182delTGA, p. D1060del; c.3625A>G, p. M1209V) [14].…”
Section: Discussionsupporting
confidence: 60%
“…However, the patients in this study did appear to benefit from deep-brain stimulation (DBS), as did another p.418W patient reported by Meijer et al [14]. Zech et al [15] identified seven early-onset generalised dystonia cases with novel ADCY5 mutations (c.2180G>A; p. R727K; c.1378A>T, p. I460F; c.1196C>T, p. P399L; c.1400A>G, p. N467S; c.3177_3182delTGA, p. D1060del; c.3625A>G, p. M1209V) [14]. Notably, the authors of this report highlight that the ADCY5 clinical spectrum may extend to isolated and focal dystonia presentations.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…To identify genetic variants responsible for the probands' phenotypes via a nontargeted approach, whole‐exome sequencing (WES) was conducted on genomic DNA from all probands using the SureSelect All Exon system (Agilent Technologies, Santa Clara, California) for exome capture and the HiSeq2500 platform (Illumina, San Diego, California) for sequencing. Sequence alignment, genotype calling, and variant annotation were performed as described earlier . In probands 1 and 2, parental DNA samples were included for trio‐based WES analysis, and de novo alterations were extracted using validated in‐house scripts .…”
Section: Participants and Methodsmentioning
confidence: 99%
“…Generalized dystonia has a strong, albeit considerably variable genetic basis . Despite the introduction of powerful sequencing techniques, a substantial proportion of cases remain genetically unsolved . Recently, we and an independent team delineated a novel autosomal‐dominant generalized dystonia syndrome, characterized molecularly by a monoallelic defect in the epigenetic regulator gene KMT2B (Mendelian Inheritance in Man (MIM): 606834).…”
mentioning
confidence: 99%